Comparison of Placental Abruption Between Multipara and Grand Multipara - Niaz, Ammara; Zafar, Al Fareed; Noor, Shagufta; Javed, Naureen (Annals of Punjab Medical College, 2016)
Objective of study is to compare the frequency of placenta abruption between Grand multipara and multipara. Study design: Descriptive Case Series. Place and duration of study: Department of Gynecology & Obstetrics Allied Hospital, Faisalabad Medical University, Faisalabad. Period of study: 6 months from 1st Jan 2016 to 30th June 2016. Methodology: After taking approval from hospital ethical committee a patients admitted in emergency who fulfilled inclusion criteria were enrolled in this study. Parity was recorded, based on which patients were divided into multipara groups according to operational definition. Placenta abruption was recorded and results compared. Results: Total 425 patients fulfilling inclusion and exclusion criteria were enrolled in our study. Out of these 425 patients, 11 patients had placenta abruption (2.58%). Comparison between grand multipara andmultipara showed that 3 (0.71%) cases of placenta abruption noted in multipara and 8 (1.88%) were in grandmultipara. P value was calculated as 0.02. Conclusion: It was concluded that frequency of placenta abruption and its consequences can be reduced by proper and effective family planning education and improving antenatal care.